Secondary frequency regulation in power networks with on-off load side participation - Kasis, Andreas; Monshizadeh, Nima; Lestas, Ioannis (My University, 2018)
We study the problem of secondary frequency regulation where ancillary services are provided via load-side participation. In particular, we consider on-off loads that switch when prescribed frequency thresholds are exceeded in order to assist existing secondary frequency control mechanisms. We show that system stability is not compromised despite the switching nature of the loads. However, such control policies are prone to Zeno-like behavior, which limits the practicality of these schemes. As a remedy to this problem, we propose a hysteresis on-off policy and provide stability guarantees in this setting. We provide numerical investigations of the results on a realistic power network.
Keywords: Electric network analysis; System stability; Electric power transmission networks; Ancillary service; Control mechanism; Control policy; Secondary frequency regulation